A culture of light : cinema and technology in 1920s Germany - Guerin, Frances (Minneapolis, Minn. : University of Minnesota Press ; [Bristol] : [University Presses Marketing, distributor], 2005)
In Frances Guerin's history of German silent cinema of the 1920s, the use of light is the pivot around which a new national cinema and culture emerges. Guerin's interpretations center on use of light in films such as Metropolis (1926) and Der Golem (1920) and we see how light is the substance of image composition, the narrative structuring device, and the thematic concern. Choice Outstanding Academic Title.
Acknowledgments; Introduction; 1. The Electrification of Life, Cinema, and Art; 2. Bringing Cinema to Life through Light: German Film to World War I; 3. Legends of Light and Shadow: The Mythical Past in Algol and Schatten; 4. The Spell of Light: Cinema as Modern Magic in Faust, Der Golem, Siegfried, and Metropolis; 5. Reformulations of Space through Light in Die StraBe, Jenseits der StraBe, and Am Rande der Welt; 6. Dazzled by the Profusion of Lights: Technological Entertainment in Varieté and Sylvester; Conclusion; Notes; Index.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Motion pictures -- Germany -- History -- 20th century; Cinematography -- Lighting -- Germany -- History -- 20th century; Cinéma -- Allemagne -- Histoire -- 20e siècle.; Cinéma -- Éclairage -- Allemagne -- Histoire -- 20e siècle.; PERFORMING ARTS -- Film & Video -- History & Criticism; Cinematography -- Lighting; Motion pictures; Germany; 1900-1999; History